Race, Social Cohesion and the Changing Politics of Citizenship. (1st November 2004) - Shukra, Kalbir; Back, Les; Keith, Michael; Khan, Azra; Solomos, John
Abstract : The relationship between race, social cohesion and citizenship has become an important issue in recent political and policy debates. In this paper these questions are explored in the context of the changing forms of ethnic minority political engagement and participation that have evolved in the past two decades. We suggest that there are growing tensions in policy debates about the boundaries and limits of multicultural policies, particularly focused around the issue of social cohesion.